2023
DOI: 10.1038/s41467-023-35862-0
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 viral entry and replication is impaired in Cystic Fibrosis airways due to ACE2 downregulation

Abstract: As an inherited disorder characterized by severe pulmonary disease, cystic fibrosis could be considered a comorbidity for coronavirus disease 2019. Instead, current clinical evidence seems to be heading in the opposite direction. To clarify whether host factors expressed by the Cystic Fibrosis epithelia may influence coronavirus disease 2019 progression, here we describe the expression of SARS-CoV-2 receptors in primary airway epithelial cells. We show that angiotensin converting enzyme 2 (ACE2) expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
2
20
1
1
Order By: Relevance
“…Using two independent protocols at two virology laboratories, we observed donor‐to‐donor differences, but comparable replication levels of SARS‐CoV‐2 in CF versus non‐CF monolayers under conditions studied here (Figure 1C,D). This result contrasts findings from others 80 …”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Using two independent protocols at two virology laboratories, we observed donor‐to‐donor differences, but comparable replication levels of SARS‐CoV‐2 in CF versus non‐CF monolayers under conditions studied here (Figure 1C,D). This result contrasts findings from others 80 …”
Section: Resultscontrasting
confidence: 99%
“…This result is similar to a previous report in which Bezzerri et al showed ACE2 was deficient in CF primary airway epithelia as judged by quantitative immunofluorescence. The same report indicated decreased SARS‐CoV‐2 replication and diminished IL6 expression in the CF samples 80 . TMPRSS2 RNA expression was variable (Figure 1A), but (unlike ACE2) demonstrated moderate correlation with SARS‐CoV‐2 replication (Figure 1B, R 2 = .76), compatible with importance of secreted proteases during the viral infectious cycle 30,81 .…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…For example, Bezzerri et al found that downregulation of ACE2 leads to impaired replication of SARS-CoV-2. [73] Tu et al found that ACE2 localized in the nucleus is closely related to the replication of SARS-CoV-2. [74] In addition, John et al reported that the expression of ACE2 not Journal of Bio-X Research only determines whether an individual is infected but also in turn regulates the host's response and outcome.…”
Section: Research Articlementioning
confidence: 99%